A Survey of Physicians' Knowledge and Adherence to the Diagnostic Criteria for Fibromyalgia. Issue 6 (21st November 2017) - Kumbhare, Dinesh; Ahmed, Sara; Sander, Tori; Grosman-Rimon, Liza; Srbely, John
Abstract: Objective: In 2010, Wolfe et al. demonstrated poor physician use of the 1990 fibromyalgia diagnostic criteria and proposed the 2010 criteria to address physician shortcomings. No follow-up studies have investigated whether physicians are using these criteria. The purpose of this study was to provide seminal data on physician knowledge and use of the fibromyalgia diagnostic criteria. Methods: This was an observational study. A questionnaire was distributed to a convenience sample of physicians who diagnose chronic pain conditions. Physician agreement was evaluated with statements testing their knowledge on the fibromyalgia criteria, and then intraclass correlations were calculated to determine the homogeneity of physicians' responses. We also determined whether physician knowledge was impacted by their specialist training and clinical experience. Results: Physician responses varied between correct and incorrect agreement on most questions. Physician specialist training was positively correlated with knowledge of the criteria. Physician knowledge overall was not comprehensive and was very poor for the 1990 and 2010 criteria. Fifty-one percent of physicians used a set of criteria in their practice, and 49% used their clinical acumen. Conclusions: Physicians do not have adequate and homogenous knowledge of the fibromyalgia diagnostic criteria. Approximately half of physicians did not adhere to the criteria. Poor knowledge and adherence to the criteria may increase diagnosis delays and misdiagnoses. Knowledge translation strategies should be implemented to address this problem.